-2(-7W+3)-8W=2(W-5)-6

Simple and best practice solution for -2(-7W+3)-8W=2(W-5)-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(-7W+3)-8W=2(W-5)-6 equation:


Simplifying
-2(-7W + 3) + -8W = 2(W + -5) + -6

Reorder the terms:
-2(3 + -7W) + -8W = 2(W + -5) + -6
(3 * -2 + -7W * -2) + -8W = 2(W + -5) + -6
(-6 + 14W) + -8W = 2(W + -5) + -6

Combine like terms: 14W + -8W = 6W
-6 + 6W = 2(W + -5) + -6

Reorder the terms:
-6 + 6W = 2(-5 + W) + -6
-6 + 6W = (-5 * 2 + W * 2) + -6
-6 + 6W = (-10 + 2W) + -6

Reorder the terms:
-6 + 6W = -10 + -6 + 2W

Combine like terms: -10 + -6 = -16
-6 + 6W = -16 + 2W

Solving
-6 + 6W = -16 + 2W

Solving for variable 'W'.

Move all terms containing W to the left, all other terms to the right.

Add '-2W' to each side of the equation.
-6 + 6W + -2W = -16 + 2W + -2W

Combine like terms: 6W + -2W = 4W
-6 + 4W = -16 + 2W + -2W

Combine like terms: 2W + -2W = 0
-6 + 4W = -16 + 0
-6 + 4W = -16

Add '6' to each side of the equation.
-6 + 6 + 4W = -16 + 6

Combine like terms: -6 + 6 = 0
0 + 4W = -16 + 6
4W = -16 + 6

Combine like terms: -16 + 6 = -10
4W = -10

Divide each side by '4'.
W = -2.5

Simplifying
W = -2.5

See similar equations:

| 2(x-7)=8+3x | | -1=k-9 | | x-3/10=4x | | -3c+7=-17 | | 7n+x=3x-n | | 6n+3=-4n+7 | | x²√25/289 | | 12x-3y=-36 | | (6x-4)(4n-5)= | | -78=3j+7-8j | | 25=40+s | | 27x=28 | | 4x^2+14-210=0 | | p-3/8 | | 3x/y=6 | | X+17=151 | | (12-5i)(7i+5)= | | A+2(y+3)=y+7 | | 6f-4+2f=20 | | 6x-8+15=-9 | | -6x-3x=5(x-5)-3(7x+1) | | 3(-0.8+0.4y)+2y=0 | | (7r-4)(r+5)-(2r-1)(r+5)= | | 2(3y+7)=44 | | (3x+1)+(8x-24)= | | 0=.333x+4 | | -y^2=0 | | 14u-9u=45 | | 13=y+20 | | 3(-5+5x)-2x=11 | | t^2-2t=(t+3) | | 5+4w=-3 |

Equations solver categories